2022
DOI: 10.1016/j.ekir.2021.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Implantable Loop Recorder Monitoring and the Incidence of Previously Unrecognized Atrial Fibrillation in Patients on Hemodialysis

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Arrhythmias are common in patients with ESKD and related to outcome. Data from implantable loop recorders showed a high prevalence of atrial fibrillation (AF) but also stressed the importance of bradyarrhythmias as potential harbingers of sudden cardiac death in this population [ 13 , 14 ]. To the best of our knowledge, there are no published studies on arrhythmia detection using non-invasive, wearable devices specifically in this population.…”
Section: Wearable Devices For Diagnosis and Monitoring In Ckdmentioning
confidence: 99%
“…Arrhythmias are common in patients with ESKD and related to outcome. Data from implantable loop recorders showed a high prevalence of atrial fibrillation (AF) but also stressed the importance of bradyarrhythmias as potential harbingers of sudden cardiac death in this population [ 13 , 14 ]. To the best of our knowledge, there are no published studies on arrhythmia detection using non-invasive, wearable devices specifically in this population.…”
Section: Wearable Devices For Diagnosis and Monitoring In Ckdmentioning
confidence: 99%
“…The Monitoring in Dialysis study 23 supported these findings and further reported a median of 7 days with AF but ranging from 1-161 days. 24 Subclinical AF has not been characterized in peritoneal dialysis cohorts, although there is no difference in AF incidence between hemodialysis and peritoneal dialysis cohorts beyond 90 days after dialysis commencement. 25 In a population where CHA 2 DS 2 -VASc scores are high, the interaction between clinical risk factors and AF type or burden may inform stroke risk.…”
Section: Stroke Risk Assessment In Kidney Failurementioning
confidence: 99%
“…Some episodes will self-terminate, but subclinical AF may go unrecognized for extended periods of time. 24 The prognostic significance of these episodes is unclear, and there is likely to be significant clinician variability in OAC practice in this population.…”
Section: Stroke Risk Assessment In Kidney Failurementioning
confidence: 99%
See 1 more Smart Citation